New records of Utricularia australis (Lentibulariaceae) in Ukraine - Iakushenko, D.M.; Orlov, O.O. (Український ботанічний журнал, 2015)
The data about the first findings of Utricularia australis in Ukrainian Polissia (Zhytomyr Region) are given. Ecological and coenotic patterns of this species for the new locations are presented. Species localities were represented by small artificial reservoirs in clay, peat and granite quarries, as well as ponds. It was revealed that Utricularia australis grew in four floristic associations: Utricularietum australis Müller et Görs 1960, Nitelletum mucronatae Corillion et Guerlesquin 1972, Equiseto fluviatilis-Caricetum rostratae Zumpfe 1929, Equisetetum fluviatilis NowiĔski 1930. For the first time in Ukraine, the association Utricularietum australis is reported and its characteristic is given.